Teacher’s Experience in Teaching Speaking Using Role Play Technique - Nur Raihan; Siti Sarah Fitriani; Chairina Chairina (Research in English and Education Journal, 2019)
This study aimed at analyzing the way the teacher teaches speaking using role play technique and investigating the drawback of role play steps implemented by the teacher while teaching speaking. Descriptive qualitative study was undertaken by observing and interviewing an English teacher at Fatih Bilingual School. The result of the observation was analyzed by using role play procedure proposed by Huang (2008). The result of the study revealed that there were two steps of role play that were modified by the teacher and one step that was skipped by the teacher while she implemented role play technique in teaching speaking. In conclusion, there were two steps that not related to the theory.